Program agama di Pusat Pemulihan Akhlak Jabatan Kebajikan Masyarakat (JKM): Kajian dari aspek pelaksanaan dan keberkesanan / Noor Hafizah Mohd Haridi - Noor Hafizah, Mohd Haridi (2016)

(untitled)
Jabatan Kebajikan Masyarakat (JKM) or the Social Welfare Department that is fully under the auspices of the Malaysian government, has set up Reformatory Institution which accommodates troubled adolescents especially those who are involved in juvenile cases. The institution comprises of Asrama Akhlak, Taman Seri Puteri and Tunas Bakti School. Based on the entry statistic until 2010, 1412 troubled adolescents were institutionalized with 1151 of them were Malay Muslim adolescents. As the responsible agency in providing reformation especially spiritual reformation, JKM in collaboration with JAKIM (Department of Islamic Development Malaysia) have outlined and developed Islamic Education module that serves as the foundation and principal guidelines in implementing religious program. Its implementation is synchronized in every reformation institution. This study focussed on the implemented religious program by analysing the following aspects: implementation, effectiveness and problems in the implementation concerning the trainees of the institutions. The design of the study was quantitative. Document analysis and interview were used to complement the study findings and as supporting data. The study respondents consisted of trainees and Islamic affairs officers and assistants. For the questionnaire survey, the trainees were selected using stratified random sampling method. A total of 286 trainees from eight institutions all over Malaysia were directly involved in this study. The data from the survey were analysed using Statistical Package for the Social Science (SPSS) for window (version 16.0). Overall, the study showed the religious program in the institutions was not consistently implemented. Only 17.5% of the respondents agreed the religious program was implemented between five to six times in a week. The study also found a lack of religious teacher in the institutions served as the contributing factor to the poor implementation of the religious program vii arranged by JKM. The effectiveness of the religious programs in the institutions was measured based on the level of knowledge and behaviour improvement of the trainees. Overall analysis found the level of trainees’ knowledge was high (min=4.51). Nevertheless, the trainees’ behaviour analysis result was moderately hight (min=3.02). The findings indirectly revealed that the trainees in the institutions need continuous guidance particularly in terms of the practical aspect in relation to the basics of Islam. Apparently, the outcomes of this study gave an added value to JKM’s reformatory institutions in their effort to reform the trainees. JKM should also review their Islamic Education Curriculum Module in order to ensure its relevance with the trainees’ level and at the same time should increase the number of religious teacher in each institution.